Trends and inequalities in full immunization coverage among two-year-olds in Sierra Leone, 2008–2019 - Umaru Sesay; Augustus Osborne; Hassan Benya; Camilla Bangura; Bright Opoku Ahinkorah (PLoS ONE, 2025)
Background Immunization is a cornerstone of public health, preventing numerous vaccine-preventable diseases. However, disparities in immunization coverage persist globally, particularly in low-income countries like Sierra Leone. This study aims to examine the trends and socioeconomic and geographic inequalities in full immunization coverage among two-year-olds in Sierra Leone between 2008 and 2019. Methods This study utilised data from the Sierra Leone Demographic Health Surveys conducted in 2008, 2013, and 2019. The Health Equity Assessment Toolkit software developed by the World Health Organisation was used to calculate various inequality measures, including Difference, Ratio, Population-Attributable Risk, and Population-Attributable Fraction. An assessment of inequality was conducted across six stratifiers: maternal age, maternal economic status, maternal education level, place of residence, child sex, and sub-national province. Results Between 2008 and 2013, the coverage of full immunization coverage among two-year-olds in Sierra Leone increased from 41.1% in 2008 to 73.1% in 2013; however, the coverage decreased to 50.4% in 2019. The inequality associated with maternal age, sex of the child, and sub-national level increased between 2008 and 2019. However, the results were not statistically significant for maternal age and sex of the child. Similarly, inequalities existed with economic status, education, and place of residence steadily decreased over the same period, but the results were also not statistically significant. Conclusion The study’s findings highlight the need for sustained efforts to improve immunization coverage in Sierra Leone. While there was progress between 2008 and 2013, the subsequent decline emphasizes the importance of maintaining vital immunization programs. Addressing the significant regional disparities, particularly the gap between the southern and northern regions, is recommended. This requires targeted interventions to improve access to immunization services, strengthen health systems, and address the northern region’s underlying social and economic factors. Additionally, ongoing monitoring and evaluation are essential to identify and address emerging challenges and ensure equitable access to immunization for all children in Sierra Leone.